Determination of new bioflavonoids in bergamot (Citrus bergamia) peel oil by liquid chromatography coupled to tandem ion trap–time‐of‐flight mass spectrometry. (10th October 2013) - Donato, Paola; Bonaccorsi, Ivana; Russo, Marina; Dugo, Paola
ABSTRACT A new investigation on manually extracted samples of bergamot (Citrus bergamia) essential oil was performed by high‐performance liquid chromatography coupled with an ion trap–time‐ of‐flight mass spectrometer. The study aimed to define new quality parameters for the evaluation of bergamot essential oils based on the composition of bioflavonoid. Polymethoxylated flavones were identified in manually cold‐pressed bergamot (C. bergamia) essential oil from fruits of three different cultivars ('Femminello', 'Castagnaro' and 'Fantastico') harvested in southern Italy. The separation of the oxygen heterocyclic compounds was optimized by reversed‐phase liquid chromatography on a partially porous C18 column under gradient elution. Afterwards, calibration curves were obtained for the quantitative assay using photodiode array detection, while a hybrid ion trap–time‐of‐flight mass spectrometer was used for structure elucidation, by tandem mass experiments. The methods applied for the identification and the quantitative determination were validated. The results obtained on samples of secure origin prove that the profile of the non‐volatile fraction of bergamot peel oil is characterized, in addition to the well known coumarines and psoralens, also by four polymethoxylated flavones, namely sinensetin, nobiletin, tetra‐O‐methyl‐scutellarein, and tangeretin. In particular, the identification and quantitative determination of nobiletin and tangeretin are hereby reported, for the first time, in cold‐pressed bergamot essential oil. All the essential oil manually extracted from fruits of the three most common cultivars of C. bergamia contain variable amounts of the four polymethoxyflavones, with the cv. 'Femminello' being the one with the highest total content. Copyright © 2013 John Wiley & Sons, Ltd.